(untitled) (Journal of the Institute of Agriculture and Animal Science, 2025)
Climate-Smart Agriculture (CSA) offers strategies to enhance productivity, resilience, environmental sustainability, and livelihoods in diverse agro-ecological contexts. This review synthesizes evidence from purposively selected case studies, including peer-reviewed research and institutional reports from FAO, the World Bank, CIAT, and CGIAR partners, to examine CSA adoption, practices, and outcomes. Seven CSA domains—water, energy, nutrient, carbon, weather, knowledge, and planting—were analyzed, with associated technologies and interventions evaluated for their impact on productivity, food security, environmental health, income, and climate resilience. Regional patterns of adoption varied: water-smart interventions dominated in Africa, energy-smart and renewable solutions were prominent in Latin America, and diversification and irrigation efficiency prevailed in Asia. Water-smart practices demonstrated strong gains in productivity and resilience, while energy-, nutrient-, and carbon-smart interventions primarily improved environmental sustainability. Knowledge- and weather-smart strategies significantly enhanced food security and income, and planting-smart approaches supported climate-adapted cropping. Despite progress, CSA adoption remains concentrated on a limited set of crops and technologies, highlighting opportunities for innovation, diversification, and scaling, particularly in livestock and aquaculture systems. The review underscores the potential of CSA to transform agricultural systems toward sustainability and climate resilience and provides evidence-based insights for policy and practice.